2019
DOI: 10.1186/s12889-019-7314-z
|View full text |Cite
|
Sign up to set email alerts
|

Child marriage and psychological well-being in Niger and Ethiopia

Abstract: Background Despite an understanding of the circumstances of child marriage, including how it limits agency and erodes childhood support systems, not much is known about the relationship between child marriage and mental health of child brides, especially in the sub-Saharan African context. To address this gap, we use large-scale population-based data from ever-married women aged 18–45 in Niger ( n = 2764) and Ethiopia ( n = 4149) to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 13 publications
6
86
1
6
Order By: Relevance
“…A 2012 study by Uecker found that early marriage had a negative effect on women's mental health [25]. Research by John et al and Daraz et al also showed that women who experience early marriage have psychological problems such as stress, depression and anxiety [26,27]. Many married women were unprepared to experience any of the realities of their lives and never received training on how to deal with them, which puts them under a lot of stress in the face of the realities of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2012 study by Uecker found that early marriage had a negative effect on women's mental health [25]. Research by John et al and Daraz et al also showed that women who experience early marriage have psychological problems such as stress, depression and anxiety [26,27]. Many married women were unprepared to experience any of the realities of their lives and never received training on how to deal with them, which puts them under a lot of stress in the face of the realities of life.…”
Section: Discussionmentioning
confidence: 99%
“…Because he dislikes I go somewhere alone. "(Participant,26) Girls who marry early fall out of the world of their peers and are forced to have relationships with people who have large age difference with them. This makes them less inclined to have relationships with others, which in turn leads to more social isolation.…”
mentioning
confidence: 99%
“…In addition, due to adverse physiological and psychological impact of early marriage, 41,42 we excluded couples who married before 18 years; therefore, the findings may not be generalizable to all couples. Second, there was missing data on several covariates, and also, some study participants were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The level of education has a statistically significant effect on the common mental disorder condition of married women. People with low education have limitations in coping patterns to the problems experienced [13]. While people with higher education have the ability and knowledge more to overcome the problems of life and tend to be able to overcome the problems, women with a high education will delay marriage, resulting in low fertility rates and fewer children and better mental health [4].…”
Section: Fig 1 the Symptoms Of Common Mental Disorder Among Marriedmentioning
confidence: 99%
“…Some empirical studies have found that low levels of education affect increasing common mental disorders [11], [12], [13]. People who do not work are more at risk of common mental disorders than people who work [11], [13], [14]. The level of wealth can estimate a person's financial stability [15].…”
Section: Introductionmentioning
confidence: 99%